Mubadalah Values in Plaintiff's Divorce Cases in the Religious Courts of Lampung Province and its Contribution to the Development of Indonesian Family Law - Aprilia, Diah (SMART: Journal of Sharia, Traditon, and Modernity, 2024)
This article examines the problem of the judge's granting of a divorce suit filed by the wife on the grounds that the husband committed polygamy in the Religious Court of Lampung Province. The focus of the research is to understand the legal basis used by the judge in deciding the divorce suit, as well as the mubadalah values contained in the decision and its contribution to the development of Indonesian family law. The research method used is a qualitative approach with an in-depth analysis of the case, involving interviews with judges as participants and data collection through the study of decision documents. Primary data was obtained from direct interviews, while secondary data was collected from relevant literature on polygamy and Islamic family law. The results showed that mubadalah values, which emphasize gender equality, play an important role in judges' decisions, where the application of the principles of mutual respect and justice for wives is prioritized. In addition, the contribution of these values is seen in the development of Indonesian family law that is more inclusive and responsive to gender issues. Thus, this study explains that the mubadalah theory is not only a legal basis for decision-making but also contributes to positive changes in family law in Indonesia.Keywords: Divorce Lawsuit, Family Law, Mubadalah, Religious Court, Polygamy